The influence of training status on right ventricular morphology and segmental strain in elite pre-adolescent soccer players - Unnithan, V. B.; Beaumont, A.; Rowland, T. W.; Unnithan, V. B.; Beaumont, A.; Rowland, T. W.; Sculthorpe, N.; George, K.; Lord, R.; Oxborough, D. (European Journal of Applied Physiology, 2021)
Cardiac modifications to training are a product of the genetic pre-disposition for adaptation and the repetitive haemodynamic loads that are placed on the myocardium. Elite pre-adolescent athletes are exposed to high-intensity training at a young age with little understanding of the physiological and clinical consequences. It is unclear how right ventricular (RV) structure and function may respond to this type of stimulus. The aim of this study was to compare RV structure and strain across the cardiac cycle and within individual segments in elite soccer players (SP) and controls (CON). Methods: Twenty-two highly trained, male pre-adolescent SP and 22 age-and sex-matched recreationally active individuals CON were investigated using 2D echocardiography, including myocardial speckle tracking to assess basal, mid-wall, apical and global longitudinal strain and strain rate during systole (SRS) and diastole (SRE and SRA). Results: greater RV cavity size was identified in the SP compared to CON (RVD1 SP: 32.3 ± 3.1 vs. CON: 29.6 ± 2.8 (mm/m2)0.5; p = 0.005). No inter-group differences were noted for peak global RV strain (SP: - 28.6 ± 4.9 vs CON: - 30.3 ± 4.0%, p = 0.11). Lower mid-wall strain was demonstrated in the SP compared to CON (SP: - 27.9 ± 5.8 vs. CON: - 32.2 ± 4.4%, p = 0.007). Conclusion: Soccer training has the potential to increase RV size in pre-adolescent players. The unique segmental analyses used in this study have identified inter-group differences that were masked by global strain evaluations. The clinical and physiological implications of these findings warrant further investigation.